Greenhouse Gas Lab Visit by Kenyan Policy Makers. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
On 3rd March 2015 policy makers from the Climate Change Unit in the Ministry of Environment Kenya, visited the Greenhouse Gas lab at the International Livestock Research Institute (ILRI) Nairobi. The Lab measures GHG emissions that will be presented as evidence to policy makers which will help in developing proper mitigation strategies in view of global environmental changes. Photos: S.Kilungu (CCAFS)